Complete genome sequence and comparative analysis of Acetobacter pasteurianus 386B, a strain well-adapted to the cocoa bean fermentation ecosystem - Illeghems, Koen (BioMed Central, 2013)
BACKGROUND: Acetobacter pasteurianus 386B, an acetic acid bacterium originating from a spontaneous cocoa bean heap fermentation, proved to be an ideal functional starter culture for coca bean fermentations. It is able to dominate the fermentation process, thereby resisting high acetic acid concentrations and temperatures. However, the molecular mechanisms underlying its metabolic capabilities and niche adaptations are unknown. In this study, whole-genome sequencing and comparative genome analysis was used to investigate this strain’s mechanisms to dominate the cocoa bean fermentation process. RESULTS: The genome sequence of A. pasteurianus 386B is composed of a 2.8-Mb chromosome and seven plasmids. The annotation of 2875 protein-coding sequences revealed important characteristics, including several metabolic pathways, the occurrence of strain-specific genes such as an endopolygalacturonase, and the presence of mechanisms involved in tolerance towards various stress conditions. Furthermore, the low number of transposases in the genome and the absence of complete phage genomes indicate that this strain might be more genetically stable compared with other A. pasteurianus strains, which is an important advantage for the use of this strain as a functional starter culture. Comparative genome analysis with other members of the Acetobacteraceae confirmed the functional properties of A. pasteurianus 386B, such as its thermotolerant nature and unique genetic composition. CONCLUSIONS: Genome analysis of A. pasteurianus 386B provided detailed insights into the underlying mechanisms of its metabolic features, niche adaptations, and tolerance towards stress conditions. Combination of these data with previous experimental knowledge enabled an integrated, global overview of the functional characteristics of this strain. This knowledge will enable improved fermentation strategies and selection of appropriate acetic acid bacteria strains as functional starter culture for cocoa bean fermentation processes.